Review of the genus Sacespalus Kieffer (Platygastridae: Sceliotrachelinae) with description of six new species. Issue 4 (3rd July 2020) - Veenakumari, K.; Bakker, Frederique A. A.; Mohanraj, Prashanth
ABSTRACT: The genus Sacespalus Kieffer is reported for the first time from India with descriptions of six new species viz. S. caudatus sp. n., S. elongatus sp. n., S. kalavathyae sp. n., S. kuchela sp. n., S. ocellaris sp. n. and S. nigricoxalis sp. n. along with illustrations. Hitherto described species of this genus, S. dubiosus Buhl, S. japonicus Yamagishi, S. manii Buhl, S. rufiscapus Buhl, S. rugosiceps Kieffer, S. sulawesianus Buhl et al., S. viklundi Buhl and S. vriesi Buhl are imaged for the first time (with the exception of an SEM image of the frons of S. vriesi ). A key to the species of the females of Sacespalus of the world is provided. http://zoobank.org/25BF5851-AF46-4579-9F52-3D81144BBBD2